Torch Ginger (Etlingera elatior (Jack) R.M. Smith.) Tea and the Effects of Brewing Time on Color, Volatile Compounds, Chemical Compositions and Sensory Quality - Sapbua, Dudsadee; Cholmaitri, Chalida (Journal of Food Health and Bioenvironmental Science, 2023)
The torch ginger tea made from flower of Etlingera elatior (Jack) R.M. Smith. It is a type of herbal tea (tisanes) with health benefits. The composition of volatile aroma compounds is one of the factors which induce relaxation and charming scent. The purpose of this study was to profile volatile compounds of the torch ginger tea and quality on physical, chemical, and sensory properties of torch ginger tea. The torch ginger tea infusion was prepared by adding 2 and 5 g of torch ginger tea into 100 ml of hot water (95°C) infused for 5 and 10 min and is effected by quantity and brewing time. Results showed that volatile compounds of the dried petal of the torch ginger had the highest abundance that included α-pinene, 1- dodecanol and dodecanal, respectively. The odor description were fresh, sweet, pine earthy and woody. Prolonged brewing time and enrichment quantity of the dried petal of the torch ginger decreased L*(lightness) values but increased positive a* (red) and positive b*(yellow) significantly (p < 0.05). 5 g torch ginger with 10 min brewing time had the highest chemical content consisting of the total phenolic content (206.42 mg GAE/100 g dry weight), the total anthocyanin content (0.887 mg/100 g dry weight), the ascorbic acid (0.602 mg/100 g dry weight) and DPPH (49.38 % inhibition) were significantly (p < 0.05). However, 2 g torch ginger with 10 min brewing time had the chemical content (the total phenolic, the total anthocyanin, the ascorbic acid and DPPH) as well as with the 5 g torch ginger tea with brewing time at 5 min. The sensory properties showed 5 g torch ginger tea with 10 min brewing time had high scores for color, flavor, taste and over all acceptance. Finally, 5 g torch ginger and 10 min brewing time was recommended as the best condition.